1979
DOI: 10.1677/joe.0.0810103
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the Luteinizing Hormone Releasing Effect of Luteinizing Hormone Releasing Hormone by Arginine-Vasotocin

Abstract: The concentrations of 17-oxosteroids in the spermatic venous blood of anaesthetized dogs were used as an index of LH release to assess the effects of arginine-vasotocin on the response of the canine pituitary gland to exogenous luteinizing hormone releasing hormone (LH-RH). When injected into the carotid artery, arginine-vasotocin (1.0 microgram/kg body wt) caused no significant alterations in the testicular output of 17-oxosteroids. The administration of LH-RH (5 microgram/kg body wt, a standard dose) into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

1980
1980
2010
2010

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 0 publications
1
4
1
Order By: Relevance
“…Since the testicular response to the administration of HCG was unaffected by treatment with argininevasotocin, it is likely that the suppression of testicular steroid secretion observed was due to an effect on the anterior pituitary gland and not to a direct action of arginine-vasotocin on the testes. Although it is known that arginine-vasotocin may act within the .brain to inhibit the secretion of LH (Pavel, Dorcescu, Petrescu-Holban & Ghinea, 1973;Osland, Cheesman & Forsham, 1977;Vaughan, Blask, Johnson & Reiter, 1979), the present data suggest that arginine-vasotocin is able to antagonize or to modify the action of LH-RH on the anterior pituitary gland in immature dogs, as in mature ones (Yamashita et al 1979).…”
Section: Resultscontrasting
confidence: 65%
See 3 more Smart Citations
“…Since the testicular response to the administration of HCG was unaffected by treatment with argininevasotocin, it is likely that the suppression of testicular steroid secretion observed was due to an effect on the anterior pituitary gland and not to a direct action of arginine-vasotocin on the testes. Although it is known that arginine-vasotocin may act within the .brain to inhibit the secretion of LH (Pavel, Dorcescu, Petrescu-Holban & Ghinea, 1973;Osland, Cheesman & Forsham, 1977;Vaughan, Blask, Johnson & Reiter, 1979), the present data suggest that arginine-vasotocin is able to antagonize or to modify the action of LH-RH on the anterior pituitary gland in immature dogs, as in mature ones (Yamashita et al 1979).…”
Section: Resultscontrasting
confidence: 65%
“…In our studies, the potency of arginine-vasotocin in suppressing the LH releasing activity of LH-RH appears to be greater in immature animals than in mature animals (Yamashita et al 1979) and was also approximately ten thousand times more potent than melatonin ). These findings, therefore, raise the possibility that arginine-vasotocin might also be involved in pubertal development.…”
Section: Resultssupporting
confidence: 43%
See 2 more Smart Citations
“…The inhibition of gonadal activity by AVT has also been reported in other vertebrate taxa, including reptiles and mammals [34-37]. Additionally, Yamashita et al [38] discovered that the mechanism underlying the antigonadal action of AVT in the dog involved the AVT-induced suppression of LH release by the anterior pituitary. Their study showed that AVT administered prior to LHRH inhibited testicular activity, but that AVT did not affect testicular activity when administered prior to human chorionic gonadotropin (hCG).…”
Section: Discussionmentioning
confidence: 94%